2011
DOI: 10.3325/cmj.2011.52.594
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sleep deprivation and nighttime light exposure on clock gene expression in humans

Abstract: AimTo examine the effect of acute sleep deprivation under light conditions on the expression of two key clock genes, hPer2 and hBmal1, in peripheral blood mononuclear cells (PBMC) and on plasma melatonin and cortisol levels.MethodsBlood samples were drawn from 6 healthy individuals at 4-hour intervals for three consecutive nights, including a night of total sleep deprivation (second night). The study was conducted in April-June 2006 at the University Medical Centre Ljubljana.ResultsWe found a significant diurn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…Diurnal changes at 4-hour intervals have been detected in the gene expression of circadian regulators (Per2 and Bmal1) and neurohormones (melatonin and cortisol) in human PBMC in response to alterations of light exposure and sleep deprivation (Kavcic et al, 2011). Since eyes closed rest and concurrent abnormal light exposure can occur during the practice of meditation, we explored the expression of core circadian genes before (t 1 ) and after (t 2 ) the intervention in the mindfulness meditation and control groups using a pathway-focused quantitative-real time (q-RT) PCR assay.…”
Section: Resultsmentioning
confidence: 99%
“…Diurnal changes at 4-hour intervals have been detected in the gene expression of circadian regulators (Per2 and Bmal1) and neurohormones (melatonin and cortisol) in human PBMC in response to alterations of light exposure and sleep deprivation (Kavcic et al, 2011). Since eyes closed rest and concurrent abnormal light exposure can occur during the practice of meditation, we explored the expression of core circadian genes before (t 1 ) and after (t 2 ) the intervention in the mindfulness meditation and control groups using a pathway-focused quantitative-real time (q-RT) PCR assay.…”
Section: Resultsmentioning
confidence: 99%
“…Though limited in numbers, the few of studies of sleep deprivation (SD) on depression/anxiety have been promising. SD has been shown to reverse CSD stress-induced anxiety [285] and induce phase shifts in circadian clock gene expression [286, 287]. Molecular analyses of clock gene expression in mice following SD leads to elevated Per1 and Per2 levels in cortex, basal forebrain and hypothalamus which returned to normal levels following recovery sleep [288, 289].…”
Section: Circadian/sleep Rhythm and Depressionmentioning
confidence: 99%
“…Results of a study on circadian gene mRNA expression (NR1D1, NR1D2, PER2, and PER3) in head hair follicle cells of rotating shift workers showed circadian gene expression phase delay after the second week of late shift work (27). Under short-term acute sleep deprivation (40 hours) and light conditions, PER2 mRNA expression in PBMC presented delayed phase shift and loss of circadian rhythmicity, while BMAL1 mRNA expression did not show any changes (28). James et al (22) found that a shifted sleep-wake schedule with light at night exposure significantly affects circadian expression of PER1 and PER2 peripheral circadian oscillators in PBMC and centrally-driven melatonin secretion.…”
Section: Rotating Night Shift and Circadian Gene Expressionmentioning
confidence: 99%